Formulation and evaluation of Emulgel containing Coriandrum sativum seeds oil for Anti-inflammatory activity - Mohite, Shraddha; Salunkhe, Anuradha (Journal of Drug Delivery and Therapeutics, 2019)
The present work deals with the formulation and evaluation of anti-inflammatory activity containing Coriandrum sativum seeds oil. The major component of Coriandrum sativum seed oil is linalool (60-70%) and this linalool content is suitable for anti-inflammatory activity. Our main purpose is to treat inflammation at faster rate with minimum side effects. During formulation and development of any new dosage form the foremost common perplexity featured from hydrophobic behavior of medication that ultimately results in poor water solubility and bioavailability issues. Such types of problems are overcome by incorporating Coriandrum sativum seeds oil emulsion into gel base as 1:1 proportion to obtained a emulgel. Emulsion was prepared by using 32 factorial design in which peppermint oil and span 20 were selected as two factors. The emulgel was prepared by incorporating optimized batch of emulsion (F9 batch ) into gel base as 1:1 proportion and evaluated for their physical examination, pH, viscosity, extrudability, swelling index, drug content, In-vitro diffusion study, In- vivo anti-inflammatory study and stability study.Keywords: Anti-inflammatory activity, Coriandrum sativum, Emulgel, Linalool, O/W type emulsion.